Communication of the National Police of the Republic of Indonesia in Handling Radicalism - Andi Febri Herawati; Jenny Ratna Suminar; Edwin Rizal; Ninis Agustini Damayani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
Radicalization can lead to acts of terrorism so the government has to combat it. This study aims to investigate the communication of the National Police in suppressing radicalism in the Poso District. This study used qualitative methods and the data were collected by in-depth interviews. The population of this study was terrorist convicts, former terrorist convicts, families of terrorists and ex-terrorists, and all parties involved in handling radicalism in Poso District determined using the purposive sampling technique. Then, the data were analyzed by process coding, descriptive coding, and value coding. The results showed that the communication between the National Police in suppressing the growth and development of radicalism in Poso District is still being performed and showed effective results. Further, the radicalism in this district was caused by revenge and injustice which made people easily get recruited by Mujahidin Indonesia Timur (MIT) to carry out acts of radicalism that led to terrorism. The National Police has used social media such as Facebook, Instagram, and Twitter to suppress the growth and development of radicalism.